Further characterisation of an experimental model of tendinopathy in the horse. (28th February 2013) - Cadby, J. A.; David, F.; van de, C.; Bosch, G.; van, P. R.; Snedeker, J. G.; van, H. T. M.
Summary Reasons for performing study Injuries in energy‐storing tendons are common in both horses and man. The high prevalence of reinjury and the relatively poor prognosis for returning to preinjury performance levels warrant further research, for which well characterised models would be very helpful. Objectives Given the clinical similarities in tendinopathy of energy‐storing tendons, we hypothesised that a recently developed experimental model of equine tendon injury would display many of the characteristics of clinical tendinopathy and could therefore be of use for both species, thus providing comparative insight to the human condition and offering direct potential impact to equine medicine. Study design In vivo experimental study. Methods Surgical lesions were created in the superficial digital flexor tendon (SDFT) of 6 horses. Clinical examination, as well as biochemistry, histology and immunohistochemistry were performed on the harvested samples at 6 weeks post surgery. Results Disrupted collagen fibres, increased glycosaminoglycan content, increased presence of tenocytes with plump nuclei, the scarcity of inflammatory cells, increased matrix metalloproteinase (MMP) activity and neovascularisation were observed and found to be consistent with clinical tendinopathy. Conclusion and relevance This model displays the key features of the most common human and equine degenerative tendon disorders and is therefore an appropriate, if still imperfect, model of tendinopathy.